Physical activity & health an interactive approach - Kotecki, Jerome Edward (Jones & Bartlett Learning, 2018)
Physical Activity & Health, Fifth Edition assists and encourage students in developing a personalized physical activity and health plan based on information gleaned from the latest scientific evidence and research. The text uses a distinct interactive approach that instills confidence in students to improve their health and well-being. Through its clear and systematic coverage of the essentials of personal health and fitness, Physical Activity & Health equips students with the information, skills, and practical know-how to gain control of their health.